Use of social media by university accounting students and its impact on learning outcomes. (1st November 2016) - Khan, Tehmina; Kend, Michael; Robertson, Susan
ABSTRACT: The proliferation in the use of social media, such as Facebook and Twitter, among university students is well documented. With many universities providing student resources in formats suitable for iPad, laptop, and mobile phone use, the use of social media for university activities has become easier. This study explores the use of social media by university accounting degree students to support their academic activities in an informal setting. It explores the impact these media have on learning outcomes. Our findings suggest that university accounting degree students use social media for a number of academic-related purposes. Students establish and maintain fluid mentor/mentee relationships around academic activities related interactions through the social media. We have found that the use of Social Media is significantly associated with students' grades.